Time series analysis of the suicide attempts assisted by firefighters from 2017 to 2021 in São Paulo, Brazil - Gabriela Arantes Wagner; Tiago Regis Franco de Almeida; Adriana Leandro de Araújo; Diógenes Martins Munhoz; Pedro Gomes Andrade (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT Objective: This study aimed to analyze the time trends of suicide attempts assisted by the Fire Department of the Military Police of the State of São Paulo (Corpo de Bombeiros da Polícia Militar do Estado de São Paulo - CBPMESP) from 2017 to 2021, between sexes. Methods: This is an ecological study of 11,435 suicide attempts assisted by CBPMESP calls from January 2017 to December 2021. Three seasonal auto-regressive integrated moving average with exogenous (SARIMAX) models were adjusted considering total population, only men, and only women. Results: The total occurrences of suicide attempts were stationary in the prepandemic period but had an increased growth pattern after the pandemic began. This trend was higher among men, due to (1) lower assistance of suicide attempts during early pandemic than in the prepandemic period and (2) significant increased assistance after the beginning of vaccination against COVID-19, followed by a decrease, but with a tendency to increase, in the long-term pandemic. Conclusion: Our results indicate a growth in the long-term suicide attempts during COVID-19. The beginning of vaccination was not considered significant in the reduction of CBPMESP attendances. These results corroborate the need for a multisectoral national suicide prevention strategy to mitigate the effects of the pandemic on mental health in the State of São Paulo.